Ultrasonographic evaluation of the children with candiduria for the fungal ball: Is It necessary?. Issue 5 (October 2021) - Devrim, Fatma; Besin, Dorukhan; Colak, Rüya; Kantar, Aslı; Sorguc, Yelda; Gülfidan, Gamze; Dincel, Nida; Oral, Akgün; Calkavur, Sebnem; Ağın, Hasan; Hosgör, Münevver; Bayram, Nuri; et al.
Summary: Introduction: Imaging of the urinary tract by ultrasonography (USG) or computerized tomography scanning is recommended for detecting structural abnormalities, hydronephrosis, abscesses, emphysematous pyelonephritis, or fungus ball formation. Limited studies on the epidemiology and the imaging results of candiduria were present in the children. Aim: This study aimed to evaluate the results of renal ultrasonography imaging in hospitalized pediatric patients with candiduria. Study design: In this descriptive study, we reviewed our ultrasonography findings with hospitalized children and infants who with candiduria. The study included the period between January 2012 and December 2019. Demographic data, the previous medical history, the clinical features of the patients, ultrasonographic findings of the urinary tract system, presence of an indwelling urinary catheter, type of urinary samplings, type of candida species were retrospectively recorded. The study was approved by Institutional Review Board with the registration number 2019/366. Results: During the study period, 220 children with nosocomial candiduria were evaluated. The most common isolated candida species was Candida albicans (68.2%) and followed by C. tropicalis (9.1%). Among all patients, 2 (0.9%) had renal fungal balls associated with C. Albicans. Twenty-five patients (11.4%) had findings including internal echogenicity in the bladder (n = 12), uroepithelial thickening of the kidney (n = 10), and sediments in the renal pelvis (n = 3). Discussion: Candida albicans was the most prominent candida isolated from the patients. The fungal ball is an uncommon infection especially in children and predominantly caused by Candida species. Fungal ball in the kidney was reported as case reports especially in neonates, in immunosupressed patients, and in patients who had undergone surgical procedures. In our study, none of the patients with the fungal ball were in the neonatal period, however, the patients with fungus ball had underlying disease or condition. Our study has several limitations including a retrospective study, and the USG were not performed by a single radiologist. Besides these limitations, our findings are important to give information about the place of USG for diagnosis of the renal fungal ball in children adding valuable information to a topic in which data came from mainly case reports. Conclusions: Despite the low incidence of fungal balls reported, considering the high consequences of missing a fungal ball and elimination of it, a non-invasive method such as the renal bladder USG is still necessary for detection of fungal ball especially. More prospective studies are required for high risk groups to establish the diagnostic value of renal USG.